Northern Ireland's 1968 at 50: agonism and protestant perspectives on civil rights. Issue 1 (2nd January 2021) - Reynolds, Chris; Parr, Connal
ABSTRACT: 2018 marked the fiftieth anniversary of the seminal events of Northern Ireland's 1968: a milestone offering up an opportunity to reassess a pivotal moment in the province's recent past. This article will argue that the civil rights period has fitted into a common model of the past being used to perpetuate the divisions at the heart of Northern Irish society. It will go on to demonstrate how an innovative methodological and theoretical approach, based on oral history, education and – most crucially – agonism, has facilitated the unearthing and integration of complex and hitherto marginalised Ulster Protestant perspectives.